Getting the Picture: My Experience with Described Art - Werner, Craig (Disability Studies Quarterly, 2013)
In the latter half of the twentieth century, blind children were given little--if any--instruction in art appreciation and criticism. This lamentable gap in their education made it difficult for them not only to appreciate pictures but also to understand artistic conventions. The author relates instances of how he came to grapple with the meaning of artistic movements and how they could be enhanced by realizing their connections with parallel movements in music. A consistent process by which art can be elucidated to blind people should include explaining the basics of what is going on in the picture, putting the work in an artistic context, elaborating on seemingly minute but important details, and discussing any critical controversies about the work's interpretation. Commendable work is being done in helping the blind appreciate art, but more needs to be done. Key words: Blindness, blind museum access, verbal description of art, audio description.